Tantangan dan Hambatan Program Pengembangan Kesehatan Olahraga Untuk Lansia di Puskesmas Kota Manado - Sari, Asmala; Ratag, Gustaaf A.E.; Kandou, Grace D. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2013)
The increasing problems as well as life expectancy become a problem that needs to be considered along number of elderly is consistently over time. Elderly Health is directed to maintain and improve the health and ability to remain productive; government efforts to organize health sports of elderly in health centers in order to improve the quality of life optimally. Therefore, the purpose of this study to determine how the challenges and obstacles of Eldery Sport Health programe in Community Health Centers of Manado City.This study using qualitative methods while the informants were the head of health centers and the holder of sport health programs incommunity Health Centers of Manado City.Data collection using in-depth interviews and observational methods. This research showed only founded in four community health centers which priority to implement it, while most of others not yet implemented due to some challenging and obstacles. The conclusion in the face of challenges, health centers must prepare trained personnel comply the aspects of quantity (amount) and quality (ability), provision of funds taken from operational health support if all activity must have the fullest, facilities and infrastructure are prepared to support the implementation of sport health programs; face of barriers, community healt center should socialize with the hope of can improve knowledge of the elderly and their families in the health sport benefits, and the cooperation with community organizations in the implementation of sport healt programs can be together. Keywords: Sports Health, Elderly, Community Health Center, Challenges, Obstacles